2005
DOI: 10.1038/sj.npp.1300775
|View full text |Cite
|
Sign up to set email alerts
|

Is the Loudness Dependence of the Auditory Evoked Potential a Sensitive and Selective In Vivo Marker of Central Serotonergic Function?

Abstract: SirLang et al (2005) reported a negative association between serum brain-derived neurotrophic factor (BDNF) levels and central serotonergic neurotransmission as measured by the loudness dependence (LD) of the auditory-evoked potential (AEP). The authors suggest that low serum BDNF concentrations reflect low central serotonergic neurotransmission as indicated by the strong LD of the AEP. While these findings are interesting and may suggest a relationship between central serotonin neurotransmission and serum BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The issue of the specificity of the LDAEP for the serotonin system has largely been ignored in the literature, with several findings casting some doubt over its sensitivity to changes in serotonin function alone (Nathan et al 2005;Von Knorring and Perris 1981;Bruneau et al 1986;Juckel et al 1997;Pogarell et al 2004). For example, earlier studies on ERPs showed that a high-intensity dependence of auditory and visual evoked potentials was related to low levels of dopamine metabolites (i.e., homovanillic acid) in CSF and urine (Von Knorring andPerris 1981, Bruneau et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of the specificity of the LDAEP for the serotonin system has largely been ignored in the literature, with several findings casting some doubt over its sensitivity to changes in serotonin function alone (Nathan et al 2005;Von Knorring and Perris 1981;Bruneau et al 1986;Juckel et al 1997;Pogarell et al 2004). For example, earlier studies on ERPs showed that a high-intensity dependence of auditory and visual evoked potentials was related to low levels of dopamine metabolites (i.e., homovanillic acid) in CSF and urine (Von Knorring andPerris 1981, Bruneau et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Together these findings in humans cast doubt over the sensitivity of the LDAEP to changes in serotonergic neurotransmission and suggest that earlier findings showing abnormalities in patient groups have to be interpreted with caution with regard to their presumed link to serotonin dysfunction. Another critical component that has been largely neglected in the literature is the selectivity of the LDAEP to serotonin function (Nathan et al 2005). It has been postulated that the intensity dependence of the amplitude of AEPs to various stimulus intensities may be related to neuromodulatory systems located subcortically (Connolly 1987;Hegerl and Juckel 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The authors argued that this increase is mediated by a negative feedback via somatodendritic 5-HT1a-receptors. The question of specifi city of the association of LD and serotonin activity can be raised because in the SPECT investigation of Pogarell and colleagues, a correlation between LD and dopamine transporter availability was observed [41,44] . Additionally, animal investigations reported also some effects of the dopamine and choline system (but not noradrenaline) on the LD [26] .…”
Section: Discussionmentioning
confidence: 97%